Impairment of the water quality status in a tropical urban river. Issue 1 (2nd January 2016) - Othman, F.; Muhammad, S.A.; Azahar, S.A.H.; Alaa Eldin, M.E.; Mahazar, A.; Othman, M.S.
Abstract: The rapid development and urbanization within river catchments and along river corridors have created many problems, such as flooding and water pollution. The Penchala River Basin located in Petaling Jaya, Selangor, Malaysia, is noted as being under environmental stress due to several pollution sources, which has amplified the intention to assess the water quality. Six water quality parameters from four stations along the Penchala River were used for measurement, and the water quality index (WQI) was calculated. The average of the WQI values showed the water quality was Class I upstream, and it decreased to Class IV downstream. Land use and human activities in the basin contribute significantly to the downstream river water quality.